(3CeGdj CHf GdTLQjs - (3GHf GdTLQj , gHI Gddg Hf Ydj Hf eMeO GdMSfj, CHh GdSYGOGJ,J (B542 (3g` s ((3CSYO Hf eYGdj Hf EHQGgje s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje GdeLdS GdChd(B: (3eSCdI bGd CWGd Gddg HbGAg(B: (3EfeG hLH HfGA eG bHd GdeJcde Yf GdcSQI hGdaJM jbJVj bdHgG CdakG s
(3BNQgG (B:s
(3hbO CbhO LedkG eeQGMkG PGbHI eedhAI CMQGMG Je GdLRA GdChd ef CeGdj jJdhg aj GdLRA GdKGfj s
(3GfXQ GdLRA GdChd HQbe (B59 (3COHs
(3JHUQI GdYfhGf (B:s
(3TQM hGedGA s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B74 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B141s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B58 s
Keywords: (3GdCOHs